Characterization of fracture behavior of human atherosclerotic fibrous caps using a miniature single edge notched tensile test. (1st October 2016) - Davis, Lindsey A.; Stewart, Samantha E.; Carsten, Christopher G.; Snyder, Bruce A.; Sutton, Michael A.; Lessner, Susan M.
Graphical abstract: Abstract: One well-established cause of ischemic stroke is atherosclerotic plaque rupture in the carotid artery. Rupture occurs when a tear in the fibrous cap exposes highly thrombogenic material in the lipid core. Though some fibrous cap material properties have been measured, such as ultimate tensile strength and stress-strain responses, there has been very little, if any, data published regarding the fracture behavior of atherosclerotic fibrous caps. This study aims to characterize the qualitative and quantitative fracture behavior of human atherosclerotic plaque tissue obtained from carotid endarterectomy samples using two different metrics. Uniaxial tensile experiments along with miniature single edge notched tensile (MSENT) experiments were performed on strips of isolated fibrous cap. Crack tip opening displacement (CTOD) and stress in the un-cracked segment (UCS) were measured at failure in fibrous cap MSENT specimens subjected to uniaxial tensile loading. Both CTOD and the degree of crack blunting, measured as the radius of curvature of the crack tip, increased as tearing propagated through the tissue. Higher initial stress in the UCS is significantly correlated with higher collagen content and lower macrophage content in the fibrous cap (ρ = 0.77, P = 0.009; ρ = −0.64, P = 0.047; respectively). Trends in the data show that higher CTOD is inversely related to collagen content, though the sample size in this study is insufficient to statistically substantiate this relationship. To the authors' knowledge, this is the pioneering study examining the fracture behavior of fibrous caps and the first use of the CTOD metric in vascular tissue. Statement of Significance: A tear in the fibrous cap of atherosclerotic plaque can lead to ischemic stroke or myocardial infarction. While there is some information in the literature regarding quantitative measures of fibrous cap failure, there is little information regarding the behavior of the tissue during failure. This study examines the failure behavior of fibrous caps both qualitatively, by examining how and where the tissue fails, and quantitatively, by measuring (a) crack tip opening displacement (CTOD) in vascular tissue for the first time and (b) uniaxial stress in the un-cracked segment (UCS). This study shows that both metrics should be evaluated when assessing plaque vulnerability.